PERANAN BIMAS DAN INMAS DALAM PENINGKATAN PEREKONOMIAN MASYARAKAT ( THE ROLE OF BINMAS AND INMAS IN INCREASING THE ECONOMY) - A.T Birowo (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 1978)
Peranan BIMAS dan INMAS dalam peningkatan perekonomian masyarakat.